Critical phenomena and estimation of the spontaneous magnetization from a mean field analysis of the magnetic entropy change in La0.65Eu0.05Sr0.3Mn0.95Cr0.05O3. (February 2016) - Bellouz, R.; Oumezzine, Ma.; Hlil, E.K.
Graphical abstract: Highlights: Nanocrystalline sample La0.65 Eu0.05 Sr0.3 Mn0.95 Cr0.05 O3 was prepared using the Pechini sol–gel method. The La0.65 Eu0.05 Sr0.3 Mn0.95 Cr0.05 O3 exhibits a second order FM–PM phase transition. The mean-field model describes the critical properties in La0.65 Eu0.05 Sr0.3 Mn0.95 Cr0.05 O3 perovskite. Two different methodologies have been used for determining the spontaneous magnetization. Abstract: We have studied the magnetic and magnetocaloric properties of the La0.65 Eu0.05 Sr0.3 Mn0.95 Cr0.05 O3 manganite prepared by using a soft chemical method (Pechini method). This compound presents a single magnetic transition from ferromagnetic (FM) to paramagnetic (PM) phase at T C = 338 K. To investigate the nature of the magnetic phase transition, found to be of second-order, a detailed critical exponent study has been performed by dc-magnetization M (H, T) measurements around the Curie temperature T C . Modified Arrott plot method has been adopted to study the critical behavior of the compound around its transition region. The values deduced for the critical exponents β, γ and δ are close to the theoretical prediction of the mean-field model, indicating that the magnetic interactions are long-range. Moreover, we have investigated the validity and usefulness of the theoretical modeling in our compound La0.65 Eu0.05 Sr0.3 Mn0.95 Cr0.05 O3 based on the mean-field analysis of the magnetic entropy change (−Δ SM ) versus the magnetization data. Results obtained through this approach are compared to those obtained from extrapolation of the Arrott curves. An excellent agreement is found between the experimental (−Δ SM ) and the one estimated by Landau theory.